The Role of the School Literacy Movement in Understanding Indonesia Texts for Grade 3 Elementary School: Peran Gerakan Literasi Sekolah dalam Pemahaman Teks Bahasa Indonesia Kelas 3 SD - Irma Sofianti; Moch. Bahak Udin (Academia Open, 2022)
This qualitative research explores the role of the school literacy movement in improving reading comprehension of Indonesian texts among grade 3 students at SD Muhammadiyah 2 Tulangan. The study involves interviews, observations, and documentation as data collection techniques. The analysis follows Mules and Hubermen's theory of data analysis, including data reduction, presentation, conclusion drawing, and verification. The research findings indicate that the school literacy movement at SD Muhammadiyah 2 Tulangan positively impacts reading comprehension through implemented programs. Supporting factors include the active involvement of school members, students' enthusiasm, and adequate facilities. However, hindering factors include limited time for literacy activities due to the Covid-19 pandemic and children's reluctance to read. This research aims to provide valuable insights for readers and serve as a reference for future studies. Highlights: The school literacy movement plays a crucial role in improving reading comprehension among grade 3 students. Supporting factors include active participation of school members, students' enthusiasm, and adequate facilities. Hindering factors include limited time due to the Covid-19 pandemic and children's reluctance to read. Keywords: literacy culture, reading comprehension, Indonesian texts, school literacy movement, grade 3 students